Comparing Derivatives

Calculus Level 3

Let f f be an infinitely differentiable real-valued function defined on the real numbers. If f ( 1 n ) = n 2 n 2 + 1 \displaystyle f(\frac{1}{n}) =\dfrac{n^2}{n^2+1} , n = 1 , 2 , 3 , 4... n=1,2,3,4... , compute the values of the derivatives f ( k ) ( 0 ) , k = 1 , 2 , 3... f^{(k)}(0),k=1,2,3... , but only when k k is odd.

453 967 500 123 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Jc 506881
Feb 1, 2018

The strategy for this problem is write f ( 1 n ) f(\frac{1}{n}) in terms of the Taylor expansion of f f about x = 0 x = 0 and then rearrange terms until we get something that allows us to make a conclusion about the odd derivatives of f f . First, note that since f f is continuous, f ( 0 ) = lim n f ( 1 n ) = lim n n 2 n 2 + 1 = 1 f(0) = \lim_{n \to \infty} f(\frac{1}{n}) = \lim_{n \to \infty} \frac{n^2}{n^2+1} = 1 . f ( 1 n ) = n 2 n 2 + 1 = f ( 0 ) + f ( 0 ) 1 ! n + f ( 2 ) ( 0 ) 2 ! n 2 + f ( 3 ) ( 0 ) 3 ! n 3 + n 2 n 2 + 1 = 1 + f ( 0 ) 1 ! n + f ( 2 ) ( 0 ) 2 ! n 2 + f ( 3 ) ( 0 ) 3 ! n 3 + 1 n 2 + 1 = f ( 0 ) 1 ! n + f ( 2 ) ( 0 ) 2 ! n 2 + f ( 3 ) ( 0 ) 3 ! n 3 + 1 = f ( 0 ) 1 ! n ( n 2 + 1 ) + f ( 2 ) ( 0 ) 2 ! n 2 ( n 2 + 1 ) + f ( 3 ) ( 0 ) 3 ! n 3 ( n 2 + 1 ) + 1 = f ( 0 ) 1 ! n + f ( 2 ) ( 0 ) 2 ! + ( f ( 0 ) 1 ! + f ( 3 ) ( 0 ) 3 ! ) 1 n + ( f ( 2 ) ( 0 ) 2 ! + f ( 4 ) ( 0 ) 4 ! ) 1 n 2 + ( f ( 3 ) ( 0 ) 3 ! + f ( 5 ) ( 0 ) 5 ! ) 1 n 3 + \begin{aligned} f(\frac{1}{n}) = \frac{n^2}{n^2 + 1} &= f(0) + \frac{f'(0)}{1!n} + \frac{f^{(2)}(0)}{2!n^2} + \frac{f^{(3)}(0)}{3!n^3} + \cdots \\ \frac{n^2}{n^2 + 1} &= 1 + \frac{f'(0)}{1!n} + \frac{f^{(2)}(0)}{2!n^2} + \frac{f^{(3)}(0)}{3!n^3} + \cdots \\ \frac{-1}{n^2 + 1} &= \frac{f'(0)}{1!n} + \frac{f^{(2)}(0)}{2!n^2} + \frac{f^{(3)}(0)}{3!n^3} + \cdots \\ -1 &= \frac{f'(0)}{1!n}(n^2 + 1) + \frac{f^{(2)}(0)}{2!n^2}(n^2 + 1) + \frac{f^{(3)}(0)}{3!n^3}(n^2 + 1) + \cdots \\ -1 &= \frac{f'(0)}{1!}n + \frac{f^{(2)}(0)}{2!} + \left( \frac{f'(0)}{1!} + \frac{f^{(3)}(0)}{3!} \right) \frac{1}{n} + \left( \frac{f^{(2)}(0)}{2!} + \frac{f^{(4)}(0)}{4!} \right) \frac{1}{n^2} + \left( \frac{f^{(3)}(0)}{3!} + \frac{f^{(5)}(0)}{5!} \right) \frac{1}{n^3} + \cdots \end{aligned}

The coefficients of all the odd powers of n n are zero, so f ( 0 ) = 0 f'(0) = 0 , which implies f ( 3 ) ( 0 ) = 0 f^{(3)}(0) = 0 which, in turn, implies f ( 5 ) ( 0 ) = 0 f^{(5)}(0) = 0 , and so on. Note that you can likewise determine the even derivatives of f f , but since f ( 0 ) 0 f''(0) \neq 0 , instead of all being zero, the will form an alternating sequence.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...